The Effect of Etching Times on the Surface Morphology of P-type Silicon(100) and on the Diamond-like Carbon/silicon Solar Cell Performance - Santipap Mitrawong (Science Faculty of Chiang Mai University, 2019)
Diamond-like carbon (DLC) was coated on the cleaned p-type silicon (100) substrates. The oxide layer on the silicon wafers were cleaned by etching with a mixture of C3H6O3, HNO3 and HF with various durations. The surface resistivity and roughness of the modified silicon wafers were characterized by Van der Pauw technique and atomic force microscopy (AFM), respectively. It was found that the surface resistivity and roughness of the modified wafers were dependent on the treatment time. Diamond-like carbon films were deposited on the surface of the modified silicon wafer to form the DLC/Si junction solar cells. The performance of solar cells was tested under the light intensity of 100 mW/cm2 with an air mass 1.5 (AM1.5). The power conversion efficiency of these cells increases with the surface roughness of the p-type silicon (100) substrates. The highest surface roughness of 0.246 nm generates the highest efficiency of 0.005%.